Higher incidence of acute symptomatic seizures in probable antibody-negative pediatric autoimmune encephalitis than in major antibody-positive autoimmune encephalitis - Yamada, Naoki; Inoue, Takeshi; Kuki, Ichiro; Yamamoto, Naohiro; Fukuoka, Masataka; Nukui, Megumi; Okuno, Hideo; Ishikawa, Junichi; Amo, Kiyoko; Togawa, Masao; Sakuma, Hiroshi; Okazaki, Shin (Frontiers in Neurology, 2024)
Purpose To delineate the characteristics of probable antibody-negative pediatric autoimmune encephalitis (probable Ab-negative AE), we compared the clinical features of probable Ab-negative AE to those of major antibody-positive AE. Methods We retrospectively reviewed the clinical features of 18 patients with probable Ab-negative AE, 13 with anti-N-methyl-D-aspartate receptor encephalitis (NMDARE), and 13 with myelin oligodendrocyte glycoprotein antibody-associated disease (MOGAD). Clinical characteristics, neuroimaging findings, treatments, and outcomes were analyzed. Results The age of onset and length of hospital stay were significantly higher in the NMDARE group than in the other groups (p = 0.02 and p < 0.01). Regarding initial neurological symptoms, acute symptomatic seizures in the probable Ab-negative AE group (67%) were significantly more frequent than in the NMDARE (15%) and MOGAD (23%) groups (p < 0.01). Paraclinical evidence of neuroinflammation within 1 month of disease onset revealed that single-photon emission computed tomography (SPECT) detected abnormal alterations in 14/14 (100%), cerebrospinal fluid (CSF) analysis in 15/18 (83%), and magnetic resonance imaging (MRI) in 11/18 (61%) in patients with probable Ab-negative AE. In the probable Ab-negative AE group, seven patients (39%) developed autoimmune-associated epilepsy, whereas one patient (8%) had both NMDARE and MOGAD (not statistically significant, p = 0.07). Conclusion Patients with probable Ab-negative AE exhibited acute symptomatic seizures as initial neurological symptoms significantly more frequently. They developed autoimmune-associated epilepsy more frequently than those with NMDARE and MOGAD, which was not statistically significant. SPECT within 1 month of disease onset might be a valuable surrogate marker of ongoing neuroinflammation and neuronal dysfunction, even in patients with negative MRI findings.